Behavioral flexibility is similar in two closely related species where only one is rapidly expanding its geographic range - Logan, Corina J.; McCune, Kelsey B.; Rowney, Carolyn; Lukas, Dieter (Peer Community Journal, 2025)

(untitled)
Human-modified environments are rapidly increasing, which puts other species in the precarious position of either adapting to the new challenges or, if they are not able to adapt, shifting their range to a more suitable environment. It is generally thought that behavioral flexibility, the ability to change behavior when circumstances change, plays an important role in the ability of a species to rapidly expand their geographic range. To determine whether species differences in range expansion propensity are linked to differences in behavioral flexibility, we compared two closely related species, great-tailed grackles (Quiscalus mexicanus; GTGR) and boat-tailed grackles (Quiscalus major; BTGR). GTGR are rapidly expanding their geographic range by settling in new areas, whereas BTGR are not. We previously found that GTGR are behaviorally flexible, however not much is known about BTGR behavior. Using the comparative method thus provides an ideal way to test the hypothesis that behavioral flexibility plays a key role in the GTGR rapid range expansion. We compared the behavioral flexibility of two GTGR populations (an older population where they have been breeding since 1951 in the middle of the northern expansion front: Tempe, Arizona, and a more recent population where they have been breeding since 2004 on the northern edge of the expansion front: Woodland, California) with one BTGR population from Venus, Florida (the age of the population is unknown, but likely thousands of years old), to investigate whether the rapidly expanding GTGR, particularly the more recent population, are more flexible. We found that both species, and both GTGR populations, have similar levels of flexibility (measured as food type switching rates during focal follows). Our results elucidate that, while GTGR are highly flexible, flexibility in foraging behavior may not be the primary factor involved in their successful range expansion. If this were the case, we would expect to see a rapid range expansion in BTGR as well. This comparative perspective adds further support to our previous intraspecific findings that persistence and the variance in flexibility (rather than population average flexibility) play a larger role in the edge GTGR population than in the GTGR population away from the edge. Our research indicates that the hypothesis that higher average levels of flexibility are the primary facilitators of rapid geographic range expansions into new areas needs to be revisited.